ANALISIS YURIDIS REKAMAN CLOSED CIRCUIT TELEVISION (CCTV) SEBAGAI ALAT BUKTI TINDAK PIDANA PENCURIAN DALAM KEADAAN YANG MEMBERATKAN (Studi Putusan Nomor 5/Pid.B/2022/PN.Mdn) - Bila, Nabila Nabila (Universitas Harapan Medan, 2023)
Evidence in the examination process before trial has an important position in determining whether or not a defendant can be sentenced to a crime. Evidence in criminal procedural law is guided by Articles 183 and 184 of the Criminal Procedure Code. Evidence in pretrial investigations plays an important role in deciding whether or not a defendant can be punished for committing a crime. Provisions for proving criminal procedural law are regulated in Articles 183 and 184 of the Criminal Procedure Code.Thesis writing uses a normative juridical approach and is descriptive in nature and analyzed qualitatively. As time goes by, there is very rapid development of technology and information and is also supported by advances in science, giving birth to new regulations, namely Law Number 19 of 2016 concerning Information and Electronic Transactions, which regulates electronic activities, including electronic evidence. The conclusion of the discussion is that the legal position of CCTV recordings as evidence in the crime of theft with aggravation in Decision Number 5/Pid.B/2022/PN.Mdn is that CCTV footage is used as one of the supporting evidence provided by the Prosecutor's Office to reveal the crime of theft with aggravation . The position of CCTV in the judge's consideration is included in the category of evidence that provides clues and sheds light on a criminal act committed by the defendant